Association of Social Media use with Sleep among Physiotherapy Students of Islamabad - Sidra Hanif, Zobia Kousar, Saania Kanwal Khanzada, Hafiza Sumaira Arooj, Dilawaiz Gul, Rabia Naseer, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Social media use is quick and hard to resist nowadays. Social media continue to play a significant role in an individual's life in spite of all of the technological advancements. One of the main reasons why people have insomnia in the modern society is the media. Aim: To ascertain whether University of Ibadat International University Islamabad physiotherapy students' use of social media and the quality of their sleep are related. Methodology: A descriptive cross-sectional survey was conducted from October 2022 to February 2023 among students of Ibadat International University Islamabad. Sample was raised through non-probability convenient sampling techniques. 231 participants were selected according to inclusion and exclusion criteria. Data was analyzed by SPSS 25. Result: Total participants were 112. Out of which 15(13.4%) were males and 97(86.6%) were females, 70(62.5%) were in the age group 18-20 years, 28(25%) were in the age group 21-23 years, 14(12.5%) were in the age group 24-26 years, 88 participants have low addiction; 4 with good sleep and 84 with poor sleep. Whereas 24 participants have high addiction; 1 with good sleep and 23 with poor sleep. Usage of social media 31-60 minutes per day was 2(1.8%), 61-120 minutes per day 35(31.3%) and more than 120 minutes per day was 75(67%). The study population's chi square association (p-value) was 0.709, suggesting that there was no significant correlation between social media disruption and sleep quality. Practical Implication: Smartphone use for work-related communication at night can reduce efficiency and disrupt sleep hygiene. Accessing social media on smartphones can prolong sleep onset latency, reducing overall sleep duration, and resulting in poor sleep quality and problematic patterns. Conclusion: There is no association found between social media usage and sleep among physiotherapy students and health care professionals of Ibadat International University. Keywords: sleep, social media, PSQI, BSMAS, work-related communication, prolong sleep